Frontiers in Gynecological Endocrinology : Volume 4: Pediatric and Adolescent Gynecological Endocrinology - Sultan, Charles; Genazzani, Andrea R. (ISGE Series,, 2017)
This volume provides a comprehensive, up-to-date overview on pediatric and adolescent gynecological endocrinology. It covers a very wide range of topics with a particular focus on disorders of sex differentiation, pubertal maturation, growth disorders, primary and secondary amenorrhea, menstrual disorders in adolescents and young adults, sexuality, contraception, and pregnancy. The authors are international well-known experts who document the latest clinical experience in this continuously evolving field and provide practical guidance on the evaluation and treatment of female pubertal problems. The book is published within the International Society of Gynecological Endocrinology (ISGE) Series and is based on the 2015 International School of Gynecological and Reproductive Endocrinology (ISGRE) Summer Course. It will be an invaluable reference for gynecologists, endocrinologists, pediatricians, and experts in women's health.